Role of Optimism in Self Esteem and Self Efficacy of Older Adults - Rawat, Rohan; Mahapatra, Mamata (International Journal of Psychosocial Rehabilitation, 2020)
Aim of the present work was to study the relationship between optimism, self-efficacy and self-esteem among older adults. Two hundred community-dwelling older adults (M=58.82, SD= 3.94) of NCR region in India, who have been living there for at least 10 years were selected as a sample for the study. Image factoring and confirmatory factor analysis were used to test the hypothesis of an association between the three variables and the impact of optimism on the other two variables. Results indicated that there is a significant positive association between optimism, self-efficacy and self-esteem in older adults. It was further revealed that optimism had a significant impact on both self-efficacy and self-esteem. The presented model of expectancy-belief shows that positive life orientation or expectancies significantly affects the good opinion about one’s character and beliefs about how well one can execute the courses of action in potential situations ensuring overall positive health.